MAIN PROBLEMS OF IMPLEMENTATION OF THE SUKHOI SUPERJET 100 PROJECT - I. Bazikova (Вестник университета)
Now the Russian aviation industry faces the task of increasing the export of civilian production, however Sukhoi Superjet 100 aircraft is the only Russian product of the civil aviation sector, being exported on international market. This project has many unsolved problems, one of which is the level of after-sales services. Investments in the development of the aircraft have not been paid off yet, and the enterprise that produces it is still unprofitable.